ADOPSI CORETAX DALAM TRANSFORMASI DIGITAL PERPAJAKAN OLEH KONSULTAN PAJAK DENGAN PENDEKATAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Amelia Rahma; Ulfa Puspa Wati Widodo (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study examines the adoption of the Coretax system in Indonesia’s digital tax transformation using the Unified Theory of Acceptance and Use of Technology (UTAUT). A qualitative descriptive method was applied through observations and interviews with six tax consultants in Surabaya. Findings show that Performance Expectancy, Social Influence, and Facilitating Conditions strongly influence acceptance, while Effort Expectancy is secondary and shaped by digital literacy and peer support. Coretax improves efficiency through integrated reporting and automation, but technical and infrastructure issues remain challenges. The study suggests that successful implementation requires not only technological readiness but also continuous training and supportive organizational culture.